Climate-induced historical drift of reference evapotranspiration in Mymensingh region of Bangladesh: Climate change impact on evapotranspiration - Mousumi, Khadiza Akhter; Mojid, Md. Abdul; Ahmad, Tanvir; Uddin, Md. Zamil; Parvez, Md. Ferdous (Journal of the Bangladesh Agricultural University, 2019)
Reference crop evapotranspiration (ETo) is essential for planning and management of irrigation to ensure optimum utilization of a region’s available water resources. ETo being an indicator of atmospheric evaporative demand provides a measure of the integrated effect of climatic parameters like solar radiation, wind, temperature and humidity. Variation of these climatic parameters over long period of time alters ETo. The modified ETo is crucial for periodic adjustment of irrigation planning and management. This study evaluated variation of ETo and contribution of the climatic parameters to ETo-variation in Mymensingh region of Bangladesh by analyzing climatic data of 28 years (1990–2017). ETo was determined by FAO Penman-Monteith method and trends of ETo and its governing climatic parameters were evaluated by MAKESENS trend model. The ETo-governing climatic parameters revealed contrasting trends, which also varied in different months of the year. Net radiation and wind speed showed decreasing trend, while temperature and saturation vapor pressure deficit showed increasing trend. In spite of contrasting contributions of the climatic parameters, their combined effect reduced ETo with a resulting decreasing trend of the monthly average daily ETo over the months of the year except July. These results enhance our understanding of the effects of climate change on ETo and can help correct-planning of water resources for irrigated agriculture. J. Bangladesh Agril. Univ. 17(2): 258–264, June 2019